2022
DOI: 10.1017/s1368980022000659
|View full text |Cite
|
Sign up to set email alerts
|

Degree of adherence to plant-based diet and total and cause-specific mortality: prospective cohort study in the Million Veteran Program

Abstract: Objective: To examine the associations between adherence to plant-based diets and mortality. Design: prospective study. We calculated a plant-based diet index (PDI) by assigning positive scores to plant foods and reverse scores to animal foods. We also created a healthful PDI (hPDI) and an unhealthful PDI (uPDI) by further separate the healthy plant foods from less-healthy plant foods. Setting: the VA Million Veteran Program. Participants: 315,919 men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Our findings are generally in line with those from previous US studies on hPDI and uPDI in relation to myocardial infarction, ischemic stroke, CVD mortality, and total mortality . Importantly, we observed that inverse associations between the hPDI and CVD end points (total CVD, myocardial infarction, and stroke) were independent of genetic disease risk.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are generally in line with those from previous US studies on hPDI and uPDI in relation to myocardial infarction, ischemic stroke, CVD mortality, and total mortality . Importantly, we observed that inverse associations between the hPDI and CVD end points (total CVD, myocardial infarction, and stroke) were independent of genetic disease risk.…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, the beneficial effects of PBDs on chronic disease risk factors found in controlled trials, and their associations with lower chronic disease risk found in prospective cohort studies provide strong support for the implementation of PBDs for chronic disease prevention. In a prospective cohort of 315,919 participants, high hPDI scores were associated with a 36% lower risk of mortality and each 10-point increase was associated with a 19% lower risk [57]. On the other hand, high uPDI scores were associated with a 41% increase in mortality risk and each 10-point increase was associated with a 15% increase in risk.…”
Section: Cvd Preventionmentioning
confidence: 94%
“…* Association with outcome was significant if p < 0.05, favorable if the highest level of the index (e.g., quartile, quintile, decile) was associated with a more favorable outcome than the lowest level, unfavorable if associated with a more unfavorable outcome. † Number of comparisons for the specific index, which exceeds the number of studies ( 95 ) because of multiple comparisons in most studies.…”
Section: Resultsmentioning
confidence: 99%